PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERORIENTASI MERDEKA BELAJAR - Ramadhani, Widya; Laurens, Theresia; Molle, Juliana S; Sapulette, Fentje (Universitas Pattimura, 2021)
The Covid-19 pandemic has changed the pattern of education. Especially with the Independent Learning Program, teachers are required to be creative and innovative, teachers must create a happy atmosphere in learning. One way is to develop learning media that makes students enthusiastic in learning online. Learning videos are audio-visual media as a teacher's tool in delivering material to make it easy for students to understand and the Canva application that can support learning materials to be more interesting. The purpose of this service is to improve the quality of teachers by developing learning media according to the independent learning program. This service is carried out offline at SD N 1 and 3 Waimital. The result of this training is that teachers are able to develop video-based learning media because it really helps clarify subject matter so that teachers can implement the Independent Learning Program